Literature Review : Kesiapsiagaan Fasilitas Kesehatan Primer Menangani Penyakit Wisatawan - I Wayan Natha Wiguna; I Putu Anda Tresna Dananta; Putu Prajata Vistara Putera; Made Kurnia Widiastuti Giri; I Kadek Artawan (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
The surge in global human mobility has positioned travel medicine as a crucial component, making primary healthcare facilities the frontline in mitigating travelers' diseases. Despite this strategic role, gaps in operational and clinical preparedness remain a major challenge. This Systematic Literature Review aims to analyze empirical evidence regarding the preparedness of primary healthcare facilities in handling travelers' diseases, focusing on human resource cognitive evaluation, structural challenges, and clinical pathway formulation. The study was conducted following the PRISMA protocol through a comprehensive search of PubMed, Scopus, and ScienceDirect databases. A total of 28 articles published in the last 10 years met the inclusion criteria and were analyzed using qualitative narrative synthesis. The synthesized results indicate that global preparedness levels are sub-optimal due to multidimensional barriers. The lack of formal travel medicine training and specific certification is the primary gap, dominantly reported by over 75% of the literature, followed by limited medical consultation time (approximately 65%). Furthermore, there is a polarization of barriers based on regional economic status; developing countries mostly struggle with basic infrastructure disparities, while facilities in developed countries paradoxically face electronic health record interoperability issues for surveillance. In conclusion, optimizing interprofessional collaboration involving nurses in travel triage and integrating travel medicine into the mandatory Continuing Medical Education (CME) curriculum are urgently needed to strengthen the resilience of the tourism health system.